A Comparative Study of Instructing Methods Regarding Japanese Bowing - Takeda, Tomoya; Kamagahara, Yuko; Lu, Xiaodan; Kida, Noriyuki; Hara, Tadayuki; Ota, Tomoko (Digital Human Modeling: Applications in Health, Safety, Ergonomics and Risk Management, 2016)
We will examine whether a difference emerges between two such teaching methods: a method whereby learners watch a traditional instructional video depicting a situation in which the bowing of an expert is filmed from the side (Group A); versus a method whereby learners watch a video of the movements in the expert’s line of sight while bowing (Group B). We could ascertain that the point of vision of the keirei bowing expert was established at approximately three meters in front of her upon the floor, and that she was able to maintain a maximum angle of 30 degrees when bending at her waist. We could discern that the line of sight video had the effect of suppressing θ1, which had previously been impacted by conformity on the parts of the subjects of Group B to also bend their necks when bending at their waists. Also, we were able to observe several cases in which the angle of test subjects’ waists was rectified such as to nearly achieve 30 degrees.